PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA SEKTOR INDUSTRI BARANG KONSUMSI YANG TERCATAT DI JAKARTA ISLAMIK INDEX (JII) - Raprayogha, Rusdi; Rusnawati, Rusnawati; Abbas, Djamila (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2017)
This study aims to determine the financial performance consisting of Current Ratio, Debt to Equity Ratio, ROA and ROE both partially and simultaneously influence to the stock prices on consumer goods industries listed at Jakarta Islamic Index (JII). This study uses secondary data quantitative form of financial report that is issued by the Indonesia Stock Exchange that includes the criteria of the companies listed at Jakarta Islamic Index are engaged in the consumer goods industry in the period of 2009-2013. Secondary data sourced from Indonesian Capital Market Directory (ICMD) and it can also be obtained from the study of literature, either in the form of textbooks or journals and articles obtained from various media. Results of this research show that: (1). Variable current ratio has a positive influence but it is not significant effect to the stock prices. (2). Debt to Equity ratio variables have a positive influence but it is not significant effect to the stock prices. (3). The Variable of Return On Asset has the most dominant influence to the stock prices. (4) The results in this study show, Return On Equity has significant influence to the stock prices. The results in this study show, Return On Asset has the most dominant influence on stock prices. Return on assets is a way of measuring the results (profits) obtained for each stock. The greater the return on assets, the ability to result the profit from each share will also increase. And Return On Equity has significant influence on stock prices. It has a positive relationship with stock prices, so the larger of the ROE, the market price is also great because of the ROE provide an indication that the decision to be received by investors will be high so that investors will be interested in buying these stocks and this will influence to the stock market price that will tend to rise ,